Clinical Assessment of Retromandibular Antero-Parotid Approach for Reduction of Mandibular Subcondylar Fractures: Report of 60 Cases and Review of the Literature - Alireza Parhiz; Milad Parvin; Sasan Sanjari Pirayvatlou (Tehran University of Medical Sciences, 2020)
This study assessed the efficacy of the retromandibular antero-parotid approach for open reduction and internal fixation (ORIF) of subcondylar fractures. Sixty patients with the mean age of 31.03 years underwent surgical reduction with a 20-25mm incision in the retromandibular area with an antero-parotid transmasseteric approach. All patients were followed between 6 to 12 months. At the end of the first week, six patients exhibited postoperative malocclusion. At the next visits, all patients had optimal occlusion. Maximal interincisal opening (MIO) of 56 patients (93.3%) was >37mm, and only four patients (6.7%) had MIO<37mm. In three patients (5%), weakness of the buccal branch of the facial nerve was noticed postoperatively. No salivary gland complications were seen. The surgical scar was hardly noticeable. Retromandibular access with transmasseteric antero-parotid approach is the technique of choice for treatment of high- and low-level subcondylar fractures with adequate visibility and direct access to the condylar area.